Analisis Indeks Kekeringan Lahan Gambut di Kabupaten Siak Menggunakan Google Earth Engine (GEE) - Rinaldi, Rinaldi; Sutikno, Sigit; Sari, Indah Permata (Departemen Teknik Sipil, Fakultas Teknik Universitas Riau, 2025)
Drought is a condition in which rainfall falls below normal for a certain period and becomes a major threat to the sustainability of peatlands, as it can increase the risk of forest fires. This study analyzes the drought index in the peatlands of Siak Regency using the Standardized Precipitation Index (SPI) method based on CHIRPS satellite data on the Google Earth Engine (GEE) platform, and evaluates the relationship between SPI values and Groundwater Table Depth (TMAT). The CHIRPS rainfall dataset used to calculate SPI spans the period from 1993 to 2024. SPI values were then compared with groundwater table depth at three locations from 2019 to 2024 to assess the relationship between the two variables. The results indicate spatial and temporal connections within the study area, with several drought periods occurring simultaneously. The most significant drought event occurred in 2019, with peak intensity in August, affecting the entire study region. Regression analysis between SPI and groundwater table depth revealed a positive relationship, indicating that when rainfall decreases or SPI values are negative, the groundwater table tends to decline. However, the correlation was relatively weak, likely influenced by other factors such as peat soil characteristics, evapotranspiration, drainage, human activities, and others. Nevertheless, the relationship between these two variables can serve as a preliminary step in utilizing SPI as an importan